پیغمبر ایک روحانی پیشوا یا سیاسی لیڈر؟ایک مستشرق کا نقطہء نظر - Fatima Noreen (Pakistan Journal of Islamic Research)
Richard Bonney believes that the messenger should be a spiritual guide instead of being a political leader. He further states that it is obligatory for a prophet or messenger to promote and maintain peace in the world. If he gives instructions for war and teaches warfare then it is nothing but a preposterous contradiction from his designated duties. This is one of the many objections raised by the orientalists on Muhammad (PBUH), the last prophet of Allah Almighty. He says that the state established by Muhammad was a mere coincidence and its political management was according to the need of the times. It should not have been made a basis for Jihad by the Muslims succsessors beacuse Muhammad had no intention to gain any victories through war. Also he did not leave any political Sunnah for his followers. Further he says that prophethood and kingship are two entirely different things. The present article endeavours to refute the claims and objections raised by Richard Bonney against the Holy Prophet Muhammad (PBUH) on the basis of Quran-o-Sunnah with logical arguments and historical facts. In this article, it has been proved that the real purpose behind the prophethood of Muhammad (PBUH) was to promote and implement a just system of governance for which the establishment of a state was mandatory. According to the ordinance of Allah, it is obligatory on every Muslim to follow the Sunnah of Muhammad (PBUH). This article also clarifies that prophethood and kingship are not different but are infact two integrated facets in the implementation of Islamic system of governance.